PENGARUH PENDAPATAN TERHADAP RETURN ON ASSETS (ROA) STUDI PADA KOPERASI TUNAS ARTHA MANDIRI CABANG GARUT - dede supian; Padlan Lukman Nulhakim (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Abstract This research was conducted to determine the problems in the financial performance of companies using profitability ratios. And aims to determine the effect of income on return on assets. Where this research took place at the Tunas Artha Mandiri cooperative, Garut Branch. The method used is quantitative descriptive research. The source of the data obtained is secondary from the 2017-2021 income statement and balance sheet for the company. By measuring using a measuring tool analysis of the correlation coefficient and test of determination. In data analysis using correlation coefficient test and determination. Where the results of the study were obtained for the correlation test with a result of 0.789 which of the results indicated that income had a strong influence on return on assets. Meanwhile, from the test of the coefficient of determination with the result of 0.63 or 63% which of these results is that income has a partial effect on the return on assets of 63% and the rest is from other factors. Thus that income affects the return on assets.